Integration of Highly Luminescent Lead Halide Perovskite Nanocrystals on Transparent Lead Halide Nanowire Waveguides through Morphological Transformation and Spontaneous Growth in Water. Issue 11 (20th January 2022) - Chen, Tao; Wang, Chong; Xing, Xinxin; Qin, Zhaojun; Qin, Fan; Wang, Yanan; Alam, Md Kamrul; Hadjiev, Viktor G.; Yang, Guang; Ye, Shuming; Yang, Jie; Wang, Rongfei; et al.
Abstract: The integration of highly luminescent CsPbBr3 quantum dots on nanowire waveguides has enormous potential applications in nanophotonics, optical sensing, and quantum communications. On the other hand, CsPb2 Br5 nanowires have also attracted a lot of attention due to their unique water stability and controversial luminescent property. Here, the growth of CsPbBr3 nanocrystals on CsPb2 Br5 nanowires is reported first by simply immersing CsPbBr3 powder into pure water, CsPbBr3− γ X γ (X = Cl, I) nanocrystals on CsPb2 Br5 −γ X γ nanowires are then synthesized for tunable light sources. Systematic structure and morphology studies, including in situ monitoring, reveal that CsPbBr3 powder is first converted to CsPb2 Br5 microplatelets in water, followed by morphological transformation from CsPb2 Br5 microplatelets to nanowires, which is a kinetic dissolution–recrystallization process controlled by electrolytic dissociation and supersaturation of CsPb2 Br5 . CsPbBr3 nanocrystals are spontaneously formed on CsPb2 Br5 nanowires when nanowires are collected from the aqueous solution. Raman spectroscopy, combined photoluminescence, and SEM imaging confirm that the bright emission originates from CsPbBr3 −γ X γ nanocrystals while CsPb2 Br5 −γ X γ nanowires are transparent waveguides. The intimate integration of nanoscale light sources with a nanowire waveguide is demonstrated through the observation of the wave guiding of light from nanocrystals and Fabry–Perot interference modes of the nanowire cavity. Abstract : Morphological transformation from CsPb2 Br5 platelets to nanowires in water is discovered and utilized to synthesize CsPb2 Br5 nanowires from CsPbBr3 powder. The integration of nanoscale light sources with nanowire waveguides through the spontaneous growth of highly luminescent CsPbBr3 nanocrystals on transparent CsPb2 Br5 nanowires provides a new platform for optical sensing and quantum communications.